Facioscapulohumeral Dystrophy: Case Report and Discussion - Castellano, Vincenzo (Springer-Verlag, 2008)
Facioscapulohumeral dystrophy (FSHD) is often cited as the third most common form of muscular dystrophy. Therefore, it should be considered in patients with complaints of progressive weakness. We present the case of a man with facial, truncal, and leg weakness that initially sought medical attention for lower back pain. Electrodiagnostic testing revealed findings in the trapezius, serratus anterior, biceps, triceps, pectoralis major, tibialis anterior, and gastrocnemius muscles consistent with a myopathic disorder. Subsequent genetic testing identified a FSHD allele size consistent with a FSHD deletion mutation. Therefore, confirming the diagnosis of FSHD. Unfortunately, no effective treatments currently exist for FSHD. However, supportive measures involving physical therapy and the use of orthotics may aid in improving function and mobility.